The bridge over the racial divide : rising inequality and coalition politics - Wilson, William J., 1935- (Berkeley : University of California Press, 1999)
Studies the rising inequality in American society and addresses the need for a progressive, multiracial political coalition to combat that inequality.
Racial antagonisms and the expanding ranks of the have-nots -- Global economic changes and the limits of the race relations vision -- Building a foundation for multiracial cooperation -- From "racial preference" to affirmative opportunity -- Bridging the racial divide and coalition politics.
Includes bibliographical references (pages 145-155) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: United States -- Race relations -- Political aspects; Racism -- Political aspects -- United States; Coalitions; African Americans -- Politics and government; African Americans -- Social conditions -- 1975-; Minorities -- Political activity -- United States; Minorities -- United States -- Social conditions; Social classes -- Political activity -- United States; États-Unis -- Relations raciales -- Aspect politique; Racisme -- Aspect politique -- États-Unis.; Coalitions; Noirs américains -- Politique et gouvernement; Noirs américains -- Conditions sociales -- 1975-; Minorités -- Activité politique -- États-Unis.; Classes sociales -- Activité politique -- États-Unis.; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; African Americans -- Politics and government; African Americans -- Social conditions; Coalitions; Minorities -- Political activity; Minorities -- Social conditions; Race relations -- Political aspects; Racism -- Political aspects; Social classes -- Political activity; United States; Ethnische Beziehungen; Sozialstruktur; USA; Etnische betrekkingen; Ongelijkheid; Politieke aspecten; Verenigde Staten; Since 1975